Factors affecting regional government capital participation in Aceh Regional Banks - RM, Mugtafillah; Indayani, Indayani; Fifi Yusmita (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2024)
This study aimed to examine the affect of fiscal capacity, profit sharing funds, excess budget financing, and dividends from regional government capital participation on regional development Aceh bank with the size of the legislature as moderating variable. The unit of research analysis is amount of regional government capital participation in Aceh Bank. Research population are 23 districts in Aceh. Hypothesis was analyzed using multiple linear regression method. It was concluded that fiscal capacity, profit sharing funds, excess budget financing and regional bank dividends had a positive effect on regional government capital participation. Meanwhile, the size of the legislature has a negative effect on government capital participation. The size of the legislature negatively and insignificantly moderates fiscal capacity but negatively and significantly moderates profit sharing funds in government capital participation. The size of the legislature has a positive and insignificant moderation of excess budget financing but has a positive and significant moderation of regional bank dividends in terms of government capital participation.